THE MODELING OF PROCESSES OIF DRY MATERIALS SEPARA- TION FOR DIFFERENT LOTS OF SPECIAL OPERATIONS IN SYN- THESIZED SEPARATORS - U.I. ERMOLJEV; Y.I. LUKINOV (Advanced Engineering Research)
A general approach of the constructing of a functioning stochastic multimeasured analytic model, describing dry materials system separation on different combinations of special technological operations forming cleaning aggregate structure is given here. This article considers dry materials separation process on a conveyor. Scelperator fulfilling one of special operations.